2017
DOI: 10.1038/s41598-017-10933-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth, structure, and luminescence properties of novel silica nanowires and interconnected nanorings

Abstract: Novel silica nanowires and interconnected nanorings were firstly synthesized on a graphite paper by typical thermal catalytic chemical vapor deposition method, using silicon and carbon black powders as raw materials. The field emission scanning electron microscopy, energy dispersive x-ray spectroscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and transmission electron microscopy were used to investigate the composition and structure characterization, which indicates that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Figure a shows a surface scanning electron microscopy (SEM) image of the sample, where the presence of nanowires (NWs) can be clearly observed. The formation of such NWs is understood to be the result of the Zn‐catalyzed reaction of plasma‐phase Si and O reactants, similar to many reported examples of the metal‐catalyzed formation of NWs that have been reported in the literature …”
Section: Resultssupporting
confidence: 76%
“…Figure a shows a surface scanning electron microscopy (SEM) image of the sample, where the presence of nanowires (NWs) can be clearly observed. The formation of such NWs is understood to be the result of the Zn‐catalyzed reaction of plasma‐phase Si and O reactants, similar to many reported examples of the metal‐catalyzed formation of NWs that have been reported in the literature …”
Section: Resultssupporting
confidence: 76%
“…A complementary XPS analysis is used to confirm for the chemical structural information. The survey spectra obtained from both particles prepared reveal the type of chemical bonds formed with the Si element 57 59 . In the deconvoluted high-resolution Si (2p) spectrum of the polymeric core particles, two strong peaks corresponding to Si-C (chemical bond of TPM) and Si-O-C (the silicon ethoxide group in the TPM) are observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that one‐dimensional materials, such as nanowires, whiskers, and fibers, exhibit unique structures and properties, which are exploited to build up nano‐scale reinforcements 26‐29 . Significant efforts have been devoted for in situ synthesizing one‐dimensional Sialon materials inside ceramic matrix materials 30‐32 .…”
Section: Introductionmentioning
confidence: 99%
“…4 So the combination of Sialon and BAS not only solves the fatal brittleness problem of BAS, but also improves the thermal performance of BAS matrix.It has been demonstrated that one-dimensional materials, such as nanowires, whiskers, and fibers, exhibit unique structures and properties, which are exploited to build up nano-scale reinforcements. [26][27][28][29] Significant efforts have been devoted for in situ synthesizing one-dimensional Sialon materials inside ceramic matrix materials. [30][31][32] In these researches,…”
mentioning
confidence: 99%